DNA Copy Number Changes in Schistosoma-Associated and Non-Schistosoma-Associated Bladder Cancer - El-Rifai, Wa’el (2000)
DNA copy number changes were investigated in 69 samples of schistosoma-associated (SA) and nonschistosoma-associated (NSA) squamous cell carcinoma (SCC) and transitional cell carcinoma (TCC) of the bladder by comparative genomic hybridization (CGH). DNA copy number changes were detected in 47 tumors. SA tumors had more changes than NSA tumors (mean, 7 vs. 4), whereas the number of changes in SCC and TCC tumors was similar. SA tumors displayed more gains than losses (1.7:1), whereas NSA tumors showed an equal number of gains and losses. Changes that were observed at similar frequencies in SCC and TCC, irrespective of the schistosomal status, included gains and high-level amplifications at 1q, 8q, and 20q and losses in 9p and 13q. These changes may be involved in a common pathway for bladder tumor development and progression independent of schistosomal status or histological subtype. Losses in 3p and gains at 5p were seen only in SCC (P < 0.01) and losses in 5q were more frequent in SA-SCC than in other tumors (P < 0.05). However, changes that were more frequent in TCC than those in SCC included gains at 17q (P < 0.01) and losses in 4q (P < 0.05) and 6q (P < 0.01). Gains and high-level amplifications at 5p were seen only in SASCC (P < 0.01), whereas gains and high-level amplifications with minimal common overlapping regions at 11q13 were more frequently seen both in SA-SCC and SA-TCC tumors (P < 0.01). In addition to the above mentioned alterations, several other changes were also seen at lower frequencies. The variations in the DNA copy number changes observed in TCC, SCC, SA, and NSA bladder carcinomas suggest that these tumors have different genetic pathways.